2018
DOI: 10.1080/20013078.2018.1461505
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of serum extracellular vesicles in liver fibrosis

Abstract: The lack of approved therapies for hepatic fibrosis seriously limits medical management of patients with chronic liver disease. Since extracellular vesicles (EVs) function as conduits for intercellular molecular transfer, we investigated if EVs from healthy individuals have anti-fibrotic properties. Hepatic fibrogenesis or fibrosis in carbon tetrachloride (CCl4)- or thioacetic acid-induced liver injury models in male or female mice were suppressed by serum EVs from normal mice (EVN) but not from fibrotic mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
85
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(96 citation statements)
references
References 68 publications
1
85
0
4
Order By: Relevance
“…Western blotting confirmed the presence of the established EV membrane markers CD63, CD81, Alix, and Flotillin (Fig. 1B) [9][10][11]. TEM illustrated the EV with the characteristic cup shaped morphology and size of~100 nm (Fig.…”
Section: Ev Characterizationmentioning
confidence: 70%
See 1 more Smart Citation
“…Western blotting confirmed the presence of the established EV membrane markers CD63, CD81, Alix, and Flotillin (Fig. 1B) [9][10][11]. TEM illustrated the EV with the characteristic cup shaped morphology and size of~100 nm (Fig.…”
Section: Ev Characterizationmentioning
confidence: 70%
“…We have shown in the current study that human breast milk-derived EVs significantly decrease the incidence and severity of NEC. EVs have a vital role in cellular communication and many other biological processes because of their ability to deliver components of their molecular payload (comprising DNA, RNA, micro-RNA and proteins) into recipient cells, which can thereby become functionally reprogrammed [8,9]. Whereas previous studies showed that enteral administration of bovine or rat breast milk-derived EVs protected the intestines from NEC in in vitro and in vivo models [5,7], our study of EVs from human breast milk and their protective role in NEC in vivo provides an important advance in the field that has clear clinical implications.…”
Section: Discussionmentioning
confidence: 99%
“…HSC fibrogenesis is stimulated by these types of hepatocyte-derived EVs [29,32,41], while other phenotypic features of activated HSC such as migration and AKT phosphorylation have been shown to be enhanced by EVs from liver sinusoidal endothelial cells [42]. On the other hand, EVs from healthy hepatocytes [43], various stem cells [44][45][46][47][48][49][50][51] or the serum of healthy mice [52] have the ability to inhibit experimental liver fibrosis, largely by suppressing inflammatory responses and/or pathways of activation or fibrogenesis in HSC. The recognition that HSC are EV targets has highlighted an important new mechanism by which fibrogenic pathways in the liver are modulated and has given a new lead for novel anti-fibrotic therapies based on suppressing the action of pro-fibrotic EVs or harnessing the actions of EVs that are intrinsically anti-fibrotic.…”
Section: Discussionmentioning
confidence: 99%
“…Proteomic analysis of EV-HLSCs showed that their cargo included various anti-inflammatory proteins such as Interleukin-10, which may have contributed to the observed beneficial effects. In addition, although yet not explored in the field of NAFLD, the use of MSC-derived EVs to arrest fibrogenesis [53,83] holds promise to treat this condition, as fibrosis is one of the most important determinants of survival. These results underscore the concept that EVs can be exploited for therapy in NAFLD/NASH.…”
Section: Evs In Nafldmentioning
confidence: 99%